2013
DOI: 10.1186/cc13091
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of noisy pressure support ventilation in patients with acute hypoxemic respiratory failure

Abstract: IntroductionThis study aims at comparing the very short-term effects of conventional and noisy (variable) pressure support ventilation (PSV) in mechanically ventilated patients with acute hypoxemic respiratory failure.MethodsThirteen mechanically ventilated patients with acute hypoxemic respiratory failure were enrolled in this monocentric, randomized crossover study. Patients were mechanically ventilated with conventional and noisy PSV, for one hour each, in random sequence. Pressure support was titrated to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
(41 reference statements)
3
29
1
Order By: Relevance
“…In agreement with our results, a recent study reported the same level of intrinsic BBV, with a coefficient of variation of V T of 13.7 Ϯ 9.1% (mean Ϯ SD), in critically ill patients ventilated with the PS mode. Interestingly, even intra-individual BBV in the present study was similar to that reported by Spieth et al 21 Increased variability in V T in critically ill patients has been associated with successful weaning from mechanical ventilation, 18,22 and the coefficient of variation of V T has been proposed as a predictor for extubation outcome. 18 In this context, our results suggest that such a prediction is not influenced by the PS level and that very low PS levels can be avoided for this assessment, reducing the occurrence of fatigue and distress in the patient.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our results, a recent study reported the same level of intrinsic BBV, with a coefficient of variation of V T of 13.7 Ϯ 9.1% (mean Ϯ SD), in critically ill patients ventilated with the PS mode. Interestingly, even intra-individual BBV in the present study was similar to that reported by Spieth et al 21 Increased variability in V T in critically ill patients has been associated with successful weaning from mechanical ventilation, 18,22 and the coefficient of variation of V T has been proposed as a predictor for extubation outcome. 18 In this context, our results suggest that such a prediction is not influenced by the PS level and that very low PS levels can be avoided for this assessment, reducing the occurrence of fatigue and distress in the patient.…”
Section: Discussionsupporting
confidence: 91%
“…Noisy PSV was associated with higher V T variability and a lower number of asynchrony events. In contrast to experimental findings, cardio-pulmonary function and spatial distribution of ventilation were comparable between conventional and noisy PSV [1]. During conventional and noisy PSV, however, V T significantly higher than 8 ml/kg predicted body weight was frequently noticed.…”
contrasting
confidence: 54%
“…In Critical Care , Spieth and colleagues [1] report for the first time the use of noisy pressure support ventilation (PSV) in patients with acute hypoxemic respiratory failure.…”
mentioning
confidence: 99%
“…The reported increase in tidal volume variability (24.4 ± 7.8 % vs. 13.7 ± 9.1 %) during variable PSV was associated with improved patient-ventilator synchrony. The externally increased tidal volume variability mimics the intrinsic healthy variability more closely than can be achieved by the patient through simple on/off triggering during conventional PSV, which may explain the improved patientventilator synchrony [48].…”
Section: Variable Assisted Mechanical Ventilationmentioning
confidence: 94%